Radiological changes and ventilatory function tests in the tea factory workers exposed to tea dust in the proximity of Kandy city : a preliminary study. - Jayawardana, P.L (My University, 1990)
There is evidence from the previous studies on blenders that those exposed to tea dust are at a higher risk of developing chronic respiratory symptoms with an associated decline in the ventilatory capacity. No such studies have been done in factory workers and therefore this preliminary survey was undertaken with the objectives of determining whether the factory workers are at risk of developing ventilatory impairment and if so the degree of impairment and how effective radiology will be in detecting such cases.

There is evidence from the previous studies on blenders that those exposed to tea dust are at a higher risk of developing chronic respiratory symptoms with an associated decline in the ventilatory capacity. No such studies have been done in factory workers and therefore this preliminary survey was undertaken with the objectives of determining whether the factory workers are at risk of developing ventilatory impairment and if so the degree of impairment and how effective radiology will be in detecting such cases.